2016
DOI: 10.1002/med.21395
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Creation of Cardioprotective and Antiarrhythmic Drugs Based on Opioid Receptor Agonists

Abstract: It has now been demonstrated that the μ, δ1, δ2, and κ1 opioid receptor (OR) agonists represent the most promising group of opioids for the creation of drugs enhancing cardiac tolerance to the detrimental effects of ischemia/reperfusion (I/R). Opioids are able to prevent necrosis and apoptosis of cardiomyocytes during I/R and improve cardiac contractility in the reperfusion period. The OR agonists exert an infarct‐reducing effect with prophylactic administration and prevent reperfusion‐induced cardiomyocyte de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 294 publications
(506 reference statements)
0
30
0
Order By: Relevance
“…Results from several studies generally support the role of PKCε activation in preconditioning, for example, agents that mimic preconditioning also activate PKCε such as adenosine, volatile anesthetics, and exogenously applied PKCε agonists [16,[25][26][27][28]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from several studies generally support the role of PKCε activation in preconditioning, for example, agents that mimic preconditioning also activate PKCε such as adenosine, volatile anesthetics, and exogenously applied PKCε agonists [16,[25][26][27][28]. …”
Section: Discussionmentioning
confidence: 99%
“…The resulting ROS then activates a second PKCε mitochondrial pool that prevents the opening of the mitochondrial permeability transition pore (MPTP). The MPTP is a large conductance channel in the inner mitochondrial membrane whose extended opening leads to the dissipation of the inner mitochondrial membrane potential, matrix swelling and rupture of the outer mitochondrial membrane, ultimately leading to necrosis [20][21][22][23][24].Results from several studies generally support the role of PKCε activation in preconditioning, for example, agents that mimic preconditioning also activate PKCε such as adenosine, volatile anesthetics, and exogenously applied PKCε agonists [16,[25][26][27][28]. …”
mentioning
confidence: 99%
“…This indicates that the cardioprotection by S. coccinea is mediated via the opioid pathway. Agonist binding to the opioid receptor usually inhibits adenylyl cyclase and activates phospholipase C signaling (26). Previous studies have shown that PLC signaling leads to the activation of the PKC and RISK kinases which are activated by salvianolic acid A and B which are phenolic compounds commonly found in salvia species (27).…”
Section: Discussionmentioning
confidence: 99%
“…31 Selective mu-opioid receptor agonists, such as fentanyl and morphine, increase the ventricular fibrillation threshold in dogs with coronary artery occlusion. 32 A meta-analysis including 1295 patients in 9 studies concluded that dexmedetomidine is associated with a lower incidence of ventricular arrhythmia after elective cardiac surgery. 33 Methohexital minimizes the possibility of potentially life-threatening cardiac arrhythmias during electroconvulsive therapy compared with thiamylal or thiopental.…”
Section: Antiarrhythmic Effects Of Anesthesia Agentsmentioning
confidence: 99%